Dutch national climate change adaptation policy through a securitization lens: Variations of securitization - Mees, Heleen; Surian, Jana (Frontiers in Climate, 2023)
Climate change has been framed as a threat to human security and has therefore become securitized, scholars argue. But what about the securitization of climate change adaptation as a policy response to fight climate change? Adaptation has risen on political agendas worldwide, and a few scholars have found some early signs of the securitization of adaptation at UN/EU levels. This paper analyzes how and to what extent adaptation has become securitized at national level, studying The Netherlands as one of the frontrunners in adaptation. We compared the levels of securitization for different adaptation issues, based on content analysis of 19 general and sectoral national policy documents and 7 in-depth interviews with national policy makers and experts. Securitization is studied with respect to the discourses used to frame the climate as a risk or threat, and the actors and tools that are put forward to address the climate risk or threat. The results show that climate change has made Dutch adaptation to flood risks even more prominent: in the two most important national policy documents climate change is framed as a wake-up call to speed up the plans and actions of the longstanding Delta program to protect The Netherlands against flooding. We also see considerable differences between the levels of securitization for different adaptation issues. Water-related adaptation issues show signs of riskification, while the same cannot be said for adaptation to heat stress and drought. Furthermore, most attention goes to the governance of adaptation in the built environment, while neglecting the social and health care domains and the need to take account of the capabilities of at-risk citizen groups.